2011
DOI: 10.5195/jwsr.2011.418
|View full text |Cite
|
Sign up to set email alerts
|

Transnational Class Formation? Globalization and the Canadian Corporate Network

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
(7 reference statements)
0
6
0
Order By: Relevance
“…Another key pattern analyzed in the literature on corporate elite networks and (transnational) elite formation is the extent to which corporate directors establish transnational ties compared to national ties (Klassen & Carroll, 2011). As proposed, the extent to which Chinese directors establish such transnational networks through affiliations with firms outside of China would be a crucial indicator of the transnationalization of the Chinese business elite, and a potential indicator of convergence towards -perhaps even integration into -Western business communities.…”
Section: Transnationalizing and Hybridizing Corporate Network Of China Incmentioning
confidence: 99%
“…Another key pattern analyzed in the literature on corporate elite networks and (transnational) elite formation is the extent to which corporate directors establish transnational ties compared to national ties (Klassen & Carroll, 2011). As proposed, the extent to which Chinese directors establish such transnational networks through affiliations with firms outside of China would be a crucial indicator of the transnationalization of the Chinese business elite, and a potential indicator of convergence towards -perhaps even integration into -Western business communities.…”
Section: Transnationalizing and Hybridizing Corporate Network Of China Incmentioning
confidence: 99%
“…Both studies found that the highest number and increase in transnational interlocks is taking place in Europe, and that most of the remaining interlock ties occur between European and North American firms. More support for these findings has been found in Burris and Staples (2012), Klassen andCarroll (2011) andCarroll (2007). A recent study of the largest 1m firms on the planet shows that a transnational interlock network is already in place.…”
Section: Development Of a Transnational Interlock Networkmentioning
confidence: 77%
“…Early findings in this literature already point to a positive relationship between firm internationalization and the existence of transnational interlocks. In a study of transnational interlock formation in large Canadian firms, Klassen and Carroll () found a slight positive relationship between the transnationalization of capital investments and firm participation in transnational interlocks. These results were probably not that strong due to the internationalization measure employed by the authors, namely the transnationalization of capital investments.…”
Section: Antecedents Of National and Transnational Interlocksmentioning
confidence: 99%